Digital transformation of business model innovation - Tsai, Wan-Yi; Su, Chaun-Jun (Frontiers in Psychology, 2022)
Because of the rising labor costs and the trade impact after joining the World Trade Organization, the textile industry in Taiwan has encountered many operational and production problems and obstacles. In addition, the lack of knowledge and resources for the digital transformation required to improve business performance has led to poor production and decision-making efficiency, and stagnant R&D for textile product innovation. In order to improve business operations, enhance customer satisfaction and experience, increase efficiency and reduce manual error, this study was conducted with senior executives and company managers in Taiwan’s textile industry as the target population. The knowledge, technological resources, and competitive pressure of digital transformation are the independent variables. The organizational innovation atmosphere is the moderating variable. The study analyzes the impact of digital transformation on the intention of enterprises. The results of the study show that the knowledge of digital transformation, technological resources, and the competitive pressure of the textile industry positively and significantly affect their perceived benefits of digital transformation. Digital transformation knowledge, technological resources, and competitive pressure will negatively and significantly affect the perceived risk of digital transformation. The perceived benefits and risks of digital transformation are related to the intention of digital transformation of enterprises. The organizational innovation atmosphere of the textile industry positively moderates the influence of perceived benefits on digital transformation intention. Finally, based on the research findings, this study provides practical recommendations to senior executives and company managers in the textile industry. It is also recommended to promote the digital transformation of related software and hardware vendors and government agencies, as well as the subsequent related research reference.